Peningkatan Ekonomi Masyarakat Melalui Usaha Kerajinan Tangan Anyaman Purun di Kampung Purun Banjarbaru - Yudistira , Fahreza; Rahmini, Noor (PPJP ULM, 2021)
This research was conducted to find out (1) What is the role of purun woven handicrafts to improve the community's economy in Kampung Purun (2) supporting and inhibiting factors of community efforts in Kampung Purun in improving the economy through the craft of purun plants. The research method used in this study is a qualitative approach—interview, Observation, and Documentation data collection techniques. Data analysis uses data triangulation. The results of research and discussion conducted on improving the community's economy through the study of purun woven craft in Kampung Purun, Banjarbaru City, then it can be concluded as follows: the role of purun woven handicrafts to improve the community's economy, which is to have great potential in absorbing labor and having the ability to utilize local raw materials. At the same time, the supporting factors and obstacles to the efforts of the community in Kampung Purun in improving the economy through the cultivation of purun plants are supporting factors, namely: The availability of sufficient raw materials, the availability of labor, the availability of sufficient capital, the smooth marketing system, the strategic and favorable geographical location. At the same time, the inhibiting factors are Lack of working capital, inadequate infrastructure.